Dynamic 5-HT2C receptor editing in a mouse model of obesity. - Harriët Schellekens (Public Library of Science (PLoS), 2012)
The central serotonergic signalling system has been shown to play an important role in appetite control and the regulation of food intake. Serotonin exerts its anorectic effects mainly through the 5-HT(1B), 5-HT(2C) and 5-HT(6) receptors and these are therefore receiving increasing attention as principal pharmacotherapeutic targets for the treatment of obesity. The 5-HT(2C) receptor has the distinctive ability to be modified by posttranscriptional RNA editing on 5 nucleotide positions (A, B, C, D, E), having an overall decreased receptor function. Recently, it has been shown that feeding behaviour and fat mass are altered when the 5-HT(2C) receptor RNA is fully edited, suggesting a potential role for 5-HT(2C) editing in obesity. The present studies investigate the expression of serotonin receptors involved in central regulation of food intake, appetite and energy expenditure, with particular focus on the level of 5-HT(2C) receptor editing. Using a leptin-deficient mouse model of obesity (ob/ob), we show increased hypothalamic 5-HT(1A) receptor expression as well as increased hippocampal 5-HT(1A), 5-HT(1B), and 5-HT(6) receptor mRNA expression in obese mice compared to lean control mice. An increase in full-length 5-HT(2C) expression, depending on time of day, as well as differences in 5-HT(2C) receptor editing were found, independent of changes in total 5-HT(2C) receptor mRNA expression. This suggests that a dynamic regulation exists of the appetite-suppressing effects of the 5-HT(2C) receptor in both the hypothalamus and the hippocampus in the ob/ob mice model of obesity. The differential 5-HT(1A), 5-HT(1B) and 5-HT(6) receptor expression and altered 5-HT(2C) receptor editing profile reported here is poised to have important consequences for the development of novel anti-obesity therapies.